Virulence and antimicrobial resistance of Salmonella spp. and Escherichia coli in the beef jerky production line. Issue 9 (21st April 2017) - Fernandes, Fernanda Pereira; Voloski, Flávia Liége Schütz; Ramires, Tassiana; Haubert, Louise; Reta, Giulia Giugliani; Mondadori, Rafael Gianella; Silva, Wladimir Padilha da; Conceição, Rita de Cássia dos Santos da; Duval, Eduarda Hallal
Abstract: Intense manipulation during beef jerky production increases the possibility of contamination with pathogenic microorganisms. This study evaluated the contamination by thermotolerant coliforms, Escherichia coli and Salmonella spp., on processing surfaces and raw materials during beef jerky production, as well as in the final product. Thermotolerant coliforms were found on all surfaces tested and in the raw material. Escherichia coli was identified in 6.7% of the surface samples, while Salmonella spp. was found in 3.3% of the surface samples and 8.6% of raw material samples. Virulence genes were detected in Salmonella spp. isolates. One Salmonella spp. isolate was resistant to sulfonamide, while one E. coli isolate was multiresistant, including the presence of resistance genes sul2, strA, strB, tetA and tetB. The presence of coliforms demonstrates failings in hygienic-sanitary procedures. The presence of pathogenic microorganisms causing foodborne diseases in the production line indicates persistent contamination in the production plant. Although the drying process applied to beef jerky should guarantee the safety of the final product, the presence of multiresistant pathogenic microorganisms, presenting virulence genes, should be a matter of concern. Because beef jerky is a ready-to-eat product, a failure in the production process may cause such microorganisms to pose a public health risk. Abstract : The paper describes the isolation of potentially dangerous and antibiotic-resistant bacteria from a beef jerky production line.